2013
DOI: 10.1007/s00213-013-3110-0
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine on D2-like receptors “reboosts” dopamine D1-like receptor-mediated behavioural activation in rats licking for a isotonic NaCl solution

Abstract: These results are consistent with the proposed hypothesis and provide support to the use of the study of licking microstructure as a valid model not only for the investigation of the mechanisms governing ingestive behaviour but also for the investigation of the mechanisms underlying behavioural activation and the related evaluation processes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 40 publications
5
22
0
Order By: Relevance
“…Ropinirole treatment also reduced the number and size of bursts, indicating lower incentive motivation in the mice and a decreased hedonic impact of the water reward. A decrease in burst size after D2‐like receptor antagonist treatment was also reported by previous studies (Canu et al., ; D'Aquila, ; D'Aquila et al., ; Galistu & D'Aquila, ; Genn et al., ; Schneider et al., ). Overall, interfering with DA D2‐like receptor signalling (by either stimulation or blockade) may suppress fluid ingestion, but the underlying cause may not be straightforward and may involve several neural mechanisms.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…Ropinirole treatment also reduced the number and size of bursts, indicating lower incentive motivation in the mice and a decreased hedonic impact of the water reward. A decrease in burst size after D2‐like receptor antagonist treatment was also reported by previous studies (Canu et al., ; D'Aquila, ; D'Aquila et al., ; Galistu & D'Aquila, ; Genn et al., ; Schneider et al., ). Overall, interfering with DA D2‐like receptor signalling (by either stimulation or blockade) may suppress fluid ingestion, but the underlying cause may not be straightforward and may involve several neural mechanisms.…”
Section: Discussionsupporting
confidence: 85%
“…Our finding that D1 agonist treatment restored the number of licks but not the number of bursts in DSI mice support this, suggesting that the recovered lick number largely reflects an increase in the hedonic impact. However, previous studies in rats suggested that D1‐like receptor signalling is involved in incentive motivation (D'Aquila, ; D'Aquila et al., ; Galistu & D'Aquila, , ). This discrepancy might reflect differences in species, drugs, or administration routes.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations